Analysis of the Influence of Main Destination Countries' GDP, Exchange Rates, International Prices and Seaweed Production on Indonesia's Seaweed Exports in 2016 - 2020 - Ulfa Dian Lestari; Siti Aisyah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
This study aims to examine the effect of gross domestic product (GDP) to the main destination countries, the rupiah exchange rate against the US dollar, international seaweed prices and Indonesian seaweed production on the volume of Indonesian seaweed exports and to determine the competitiveness of seaweed export volumes to other countries. export destination. The data analysis technique used is multiple linear regression analysis using the panel data method and competitiveness analysis using the RCA (Revealed Comparative Advantage) calculation method. The results of the study using the multiple linear regression method show that the real GDP of the main destination countries, exchange rates and Indonesian seaweed production partially have no significant effect on Indonesian seaweed exports, while international seaweed export prices partially have a significant effect on Indonesian seaweed exports. . The results of the RCA competitiveness analysis show that Indonesian seaweed exports have a comparative advantage or competitiveness in export destination countries with an RCA value of >1.